Experimental Study on the Influence of Channel Length on Wave Propagation - QIAO Jiping; WU Yueyong; HAO Fengnan; ZHAO Di; BAI Yang (Renmin Zhujiang)
In view of the scarce research on the influence of channel length on wave propagation in the port area,based on the physical model test and numerical model test of wave,this paper analyzes the relationship between the wave height and the channel length in the port area under different wave conditions.The research shows that:The wave height has basically no influence on the selection of the channel length.The critical channel length corresponding to the wave height in the port area is always 3 500 m,under which the wave height simulation effect in the port can be basically equivalent to that under the long channel condition.When the incident angle of wave is small,the critical channel length on the wave approach side is 4 000 m;and when the incident angle is large,the change of the channel length has little effect on the wave height distribution on the wave approach side.For long periods and large-angle incidence of waves,the effective area on the wave back side of the channel starts from the end of the channel,and covers the area between the incident wave direction and the channel axis;while for short periods or small-angle incidence of waves,there is no effective area on the wave back side of the short channel from the model.